Physical geology - Plummer, Charles C. (McGraw Hill, 2003)
Sadržaj: 1. Introduction to physical geology ; 2. Atoms, elements, and minerals ; 3. Igneous rocks, intrusive activity, and the origin of igneous rocks ; 4. Volcanism and extrusive rocks ; 5. Weathering and soil ; 6. Sediments and sedimentary rocks ; 7. Metamorphism, metamorphic rocks, and hydrothermal rocks ; 8. Time and geology ; 9. Mass wasting ; 10. Streams and floods ; 11. Ground water ; 12. Glaciers and glaciation ; 13. Deserts and wind action ; 14. Waves, beaches and coasts ; 15. Geologic structures ; 16. Earthquakes ; 17. Earth's interior and geophysical properties ; 18. The sea floor ; 19. Plate tectonics ; 20. Mountain belts and continental crust ; 21. Geologic resources